2019
DOI: 10.1002/solr.201900172
|View full text |Cite
|
Sign up to set email alerts
|

Perovskite Solar Cells Using Surface‐Modified NiOx Nanoparticles as Hole Transport Materials in n‐i‐p Configuration

Abstract: Modified NiOx nanoparticles (NPs) developed via surface engineering are applied to a hole transport layer (HTL) in n‐i‐p‐structured perovskite solar cells (PSCs). Hexanoic acid (HA) as a surfactant improves the dispersibility of NiOx NPs in chlorobenzene (CB). The conductivity of the NiOx‐HA film is 1.20×10−5S cm−1, which is superior to that of 2,2′,7,7′‐tetrakis(N,N‐di‐p‐methoxyphenyl‐amine)‐9,9′‐spirobifluorene (spiro‐OMeTAD) with dopants. The NiOx‐HA film shows better hole extraction properties compared wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
27
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 40 publications
0
27
0
Order By: Relevance
“…The larger V bi of devices enables PSCs to have a stronger ability to separate charges and transport and collect photo-generated carriers, yielding a higher V OC . A variety of research works have demonstrated that minimizing the interfacial charge recombination between CTL and perovskite layer can effectively enhance the V OC of PSCs (Jung et al, 2019;Kaneko et al, 2019;Aidarkhanov et al, 2020). Carrier mobility is another critical factor affecting the charge transport properties.…”
Section: The Criteria Of Effective Metal Oxide Ctlsmentioning
confidence: 99%
“…The larger V bi of devices enables PSCs to have a stronger ability to separate charges and transport and collect photo-generated carriers, yielding a higher V OC . A variety of research works have demonstrated that minimizing the interfacial charge recombination between CTL and perovskite layer can effectively enhance the V OC of PSCs (Jung et al, 2019;Kaneko et al, 2019;Aidarkhanov et al, 2020). Carrier mobility is another critical factor affecting the charge transport properties.…”
Section: The Criteria Of Effective Metal Oxide Ctlsmentioning
confidence: 99%
“…[ 18–21 ] For example, p‐type metal oxides thin films derived from high‐temperature hydrolysis and annealing have been introduced in inverted planar PSCs for achieving high device performance. [ 22–26 ] Much efforts have been made to improve hole mobility, suppress the surface defects exist in the metal oxide, [ 27–30 ] and develop low temperature processable candidates and preparation method. [ 31–33 ]…”
Section: Introductionmentioning
confidence: 99%
“…One strategy that is attracting attention is a method of manufacturing a dense oxide thin film at low temperature by a solution process, using ink in which oxide nanoparticles (NPs) having high crystallinity are well dispersed. [ 10,13,14,19 ] For this, the oxide HTM ink solution should include highly dispersed metal oxide with proper electrical properties, and non‐polar solvents, such as chlorobenzene, toluene, and chloroform, to minimize the damage to the perovskite layer during the solution deposition process. However, most metal oxides present a radically hydrophilic surface, which restricts them to dispersing non‐polar solvents.…”
Section: Introductionmentioning
confidence: 99%
“…[ 14 ] To overcome those issues, hydrophobic ligand agents for capping the inorganic NPs have been utilized to improve the dispersibility in non‐polar solvents. [ 14,19 ] But it is well known that due to their insulating properties, capping agents with long carbon chain groups interfere with charge transport and transfer. [ 10,20 ] For example, the NiO‐based HPSCs with ligand agent showed a PCE of 12.7% with a very lower fill factor ( FF ).…”
Section: Introductionmentioning
confidence: 99%